Policy of the Russian Empire in Eastern Galicia during the First World War. The national aspect - Anton Karin (Cхід, 2016)
The article discusses the main activities of the Russian authorities in Galicia during the First World War. During the war in Galicia successively occupied three of the occupying administration. This administration G. A. Bobrinsky, and F. F. Trepov, D. I. Doroshenko. Policy in the national question in each of these administrations differed in their specificity. The author of the article pays special attention to the evolution of this policy and monitors the relationship of the Russian authorities with the muscophiles and the Ukrainian national movement. The first stage Russia's policy in the region was characterized by the Providence administration Bobrinsky by relying on the Russophile movement forced Russification. Ukrainian language and culture at this stage was subjected to expulsion from the public sphere, the Ukrainian national movement was seen as an implacable enemy of Russia. In the second phase in years, the Governor-General Trepov has tended to weaken the political influence mosqueteros. In this case, the softening of the administration's policies towards the Ukrainian language and culture. The third stage of Russian policy, caused by the collapse of the monarchy, was marked by the legalization of the Ukrainian national movement and the transition of power in Galicia in the hands of his representatives, headed by Doroshenko. The Russophile movement in this period completely lost its former influence and marginalized. The work also gives a brief overview of the political situation in the region in the prewar period. Special attention is paid to the ecclesiastical policy of the administration Borinskoe because re in Galicia.